I want to apply the steepest descent method to the following integration: $$ \int_0^\infty e^{-x^2 + i \sqrt{x^2 + 1} \cdot \lambda } dx $$

It has movable saddle so I need to transform it into the standard form, something like

$$ \int_C g(z) e^{\lambda f(z) } dz $$

I know for Gamma function: $$ \Gamma(x+1)= \int_0^\infty e^{-t} t^{x} dt =\int_0^\infty e^{-t + x \ln t} dt $$ letting $t = x s$ transforms it into standard form. And for Airy function:

$$Ai(x) = \frac{1}{2 \pi} \int_{-\infty}^{\infty} e^{i (t^3/3 + x t)} dt $$

letting $t = \sqrt{x} z$ does the trick.

However, no change of variable seems to transform my integration into the standard form. For this reason I can not proceed at all. Any hint or suggestion ? Thanks!

  • $\begingroup$ You need to find the saddle point (in general there can be more than one, in that case there will be one that yields the dominant contribution). If there is a saddle point at $z = z_0$, then the contour is deformed to move through $z_0$. Then write the integrand as $f(z_0 + u)$ and integrate over $u$, you define a new variable $w$ such that $f(z_0 + u) = \exp(-w^2)$, becomes exactly a Gaussian. This then has to be multiplied by the Jacobian $\frac{du}{dw}$. $\endgroup$ – Count Iblis Mar 15 '17 at 20:12
  • $\begingroup$ defining $g(x)=e^{-x^2}$? Maybe this is too simple but definitly worth a try $\endgroup$ – tired Mar 15 '17 at 21:09
  • $\begingroup$ @AntonioVargas i came away with this cheap trick a few times, but i have no idea when it works...:( $\endgroup$ – tired Mar 15 '17 at 22:25
  • $\begingroup$ Set $x^2+1=y$. The integral in question transforms into $$ I=e\int_1^{\infty}dy\frac{y}{\sqrt{y^2-1}}e^{-y^2}e^{i\lambda y} $$ after a rescaling $y\rightarrow\lambda y$ this reads $$ I=e\lambda^2\int_{1/\lambda}^{\infty}dy\frac{y}{\sqrt{\lambda^2y^2-1}}e^{-\lambda^2(y^2+iy)} $$ which is not too far away from a form where classic steepest descent method can be applied (i think @AntonioVargas has elaborated somewhere on this site on integrals of this type, where the prefactor of the exponential is a slowly varying fiunction of $\lambda$) $\endgroup$ – tired Mar 15 '17 at 22:35
  • $\begingroup$ @tired This does not work. If you take $exp(-x^2)$ in separation, the next step of asymptotics is essentially stationary phase, and the stationary point would be $x = 0$, then $exp(-x^2) = exp(0) = 1$, which is saying the term $exp(-x^2)$ has no effect. However, this conclusion is not right. $\endgroup$ – Taozi Mar 16 '17 at 0:42

Let us here sketched a derivation.

  1. OP's integral has a saddle point at $z=0$ with angular steepest descent direction $\frac{\pi}{4}$. Therefore, inspired by the method of steepest descent, we rewrite OP's integral as $$I(\lambda) ~:=~\int_{\mathbb{R}_+}\!\mathrm{d}z~ \exp\left\{-z^2+i\lambda\sqrt{1+z^2}\right\} ~=~ \frac{e^{i\lambda}}{2}J(\lambda),\qquad \lambda~>~0, \tag{1}$$ where $$J(\lambda) ~:=~\int_{\mathbb{R}}\!\mathrm{d}z~ \exp\left\{-z^2+i\lambda\left(\sqrt{1+z^2}-1\right)\right\}~\stackrel{z=\frac{u}{\sqrt{\lambda}}\exp\left(\frac{i\pi}{4}\right)}{=}~\frac{1}{\sqrt{\lambda}}\exp\left(\frac{i\pi}{4}\right) K(\lambda),\tag{2} $$ where $$ K(\lambda)~:=~\int_{\mathbb{R}}\!\mathrm{d}u~ \exp\left\{-\frac{iu^2}{\lambda}-f_{\lambda}(u)\right\},\tag{3}$$ and where $$ -f_{\lambda}(u)~:=~i\lambda\left(\sqrt{1+\frac{iu^2}{\lambda}}-1\right) ~=~-\frac{u^2}{2} + \frac{iu^4}{8\lambda}+ O(u^6\lambda^{-2}).\tag{4} $$

  2. Let us define the non-negative function $$ f(u)~:=~\frac{u^2}{2}. \tag{5} $$ Clearly $$ f_{\lambda}(u)~\longrightarrow~ f(u)\quad\text{for}\quad\lambda~\to~ \infty \tag{6}$$ $u$-pointwise.

  3. We note that the real part is given by $$ {\rm Re}~ f_{\lambda}(u)~=~\lambda\sqrt{\frac{\sqrt{1+\frac{u^4}{\lambda^2}}-1}{2}} .\tag{7}$$ Define a non-negative function $$ g(u)~:=~ \frac{|u|}{2}~\theta(|u|\!-\!\sqrt{2}) , \tag{8}$$ where $\theta$ denotes the Heaviside step function. One may show that $$\forall\lambda\geq\frac{1}{\sqrt{2}}\forall u\in\mathbb{R}:~~ {\rm Re}~ f_{\lambda}(u) ~\geq~ g(u),\tag{9}$$ because $$\forall\lambda\geq\frac{1}{\sqrt{2}}\forall u\geq\sqrt{2}:~~ \sqrt{1+\frac{u^4}{\lambda^2}}-1 ~\geq~ \frac{u^2}{2\lambda^2}.\tag{10}$$

  4. It follows that $\exp\left\{-g(u)\right\}$ is a majorant function for the integrand (3). Lebesgue's dominated convergence theorem then shows that the corresponding integral (3) satisfies $$ K(\lambda)~\longrightarrow~ \int_{\mathbb{R}}\!\mathrm{d}u~ \exp\left\{-f(u)\right\}~=~\sqrt{2\pi} \quad \text{for} \quad\lambda~\to~ \infty. \tag{11} $$

  5. Next we can estimate corrections to any order in $1/\lambda$ we like. E.g. $$K(\lambda)~\stackrel{(3)+(4)}{=}~\int_{\mathbb{R}}\!\mathrm{d}u~ \exp\left\{-\left(\frac{i}{\lambda}+\frac{1}{2}\right)u^2\right\} \left(1 +\frac{iu^4}{8\lambda} + O(\lambda^{-2})\right)$$ $$~=~\sqrt{\frac{\pi}{\frac{i}{\lambda}+\frac{1}{2}}}+\frac{i}{8\lambda}\underbrace{\int_{\mathbb{R}}\!\mathrm{d}u~\exp\left\{-\frac{u^2}{2}\right\}u^4}_{=3\sqrt{2\pi}} + O(\lambda^{-2}) ~=~\sqrt{2\pi}\left(1 -\frac{5i}{8\lambda} + O(\lambda^{-2})\right) ,\tag{12}$$ and so forth. Hence OP's integral (1) has an asymptotic expansion

    $$ I(\lambda)~\sim~ e^{i\lambda}\frac{1+i}{2}\sqrt{\frac{\pi}{\lambda}}\left(1 -\frac{5i}{8\lambda} + O(\lambda^{-2})\right)\quad \text{for}\quad \lambda~\to~\infty .\tag{13} $$

  • $\begingroup$ Hi @Qmechanic Your solution is very beautiful. I still have two questions. 1> what's the rational behind the form of substitution in equation 2, esp. the $\exp(i \pi/4)?$ 2> In equation 12 did you separate the exponent into two groups and Taylor expand the second group? If so, why $\int_R du \exp \{-(i/\lambda + 1/2)u^2 \} u^4 = -5 \sqrt{2\pi}$? $\endgroup$ – Taozi Mar 23 '17 at 14:57
  • $\begingroup$ I updated the answer. $\endgroup$ – Qmechanic Mar 23 '17 at 16:19

Not a full answer but too long for a comment.

It appears that the saddle point at $x=0$ is dominant. There are two more but they can be avoided (and they possibly lie on the branch cuts of the integrand anyway---that would be bad).

If we make the substitution $x = u/\sqrt{\lambda}$ we get

$$ \begin{align} \int_0^\infty \exp\left\{-x^2+i\lambda\sqrt{x^2+1}\right\}dx &= \frac{1}{\sqrt{\lambda}} \int_0^\infty \exp\left\{-\frac{u^2}{\lambda}+i\lambda\sqrt{\frac{u^2}{\lambda}+1}\right\}du \\ &= \frac{e^{i\lambda}}{\sqrt{\lambda}} \int_0^\infty \exp\left\{-\frac{u^2}{\lambda}-i\lambda \left( 1-\sqrt{\frac{u^2}{\lambda}+1} \right) \right\}du. \end{align} $$


$$ \int_0^\infty \exp\left\{-\frac{u^2}{\lambda}-i\lambda \left( 1-\sqrt{\frac{u^2}{\lambda}+1} \right) \right\}du \to \int_0^\infty \exp\{iu^2/2\}\,du = \frac{1+i}{2}\sqrt{\pi} $$

as $\lambda \to \infty$, but I'm not sure how to show it at the moment. This would imply that

$$ \int_0^\infty \exp\left\{-x^2+i\lambda\sqrt{x^2+1}\right\}dx \sim \frac{(1+i)e^{i\lambda}}{2} \sqrt{\frac{\pi}{\lambda}} $$

as $\lambda \to \infty$.

  • $\begingroup$ I did a quick check of your solution in Mathematica, it appears remarkably accurate, I need more time to understand how and why the substitution works. $\endgroup$ – Taozi Mar 16 '17 at 19:20
  • $\begingroup$ Unfortunately, the result appears to be the same if you throw away the $e^{-x^2}$ term right at the beginning. $\endgroup$ – Taozi Mar 16 '17 at 19:28
  • $\begingroup$ @Taozi, I used this substitution because near $x=0$ we have $$-x^2 + i\lambda\sqrt{x^2+1} = i \lambda +\left(-1+\frac{i \lambda }{2}\right) x^2 + O(x^3),$$ and substituting $x = u/\sqrt{\lambda}$ asymptotically removes the $\lambda$-dependence from the coefficient of $x^2$. $\endgroup$ – Antonio Vargas Mar 16 '17 at 20:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.